ChemInform Abstract: Exploring a New Structure Family: Alkali Borosulfates Na5[B(SO4)4], A3[B(SO4)3] (A: K, Rb), Li[B(SO4)2], and Li[B(S2O7)2]. Issue 30 (4th July 2013) - Daub, Michael; Kazmierczak, Karolina; Gross, Peter; Hoeppe, Henning; Hillebrecht, Harald
Abstract The crystal structures of the title compounds are based on corner‐linked BO4 and SO4 tetrahedra with varying coordination of the alkali cations.